Numerical integration of the integrals based on Haar wavelets - Ahmedov, Anvarjon A.; Abdul Sathar, Mohammad Hasan (Institute of Physics Publishing, 2013)
In this work, we present a computational method for solving double and triple integrals with variable limits of integrations which is based on Haar wavelets. This approach is the generalization and improvement of the methods [3]. The advantage of this new methods is its more efficient and simple applicability than the previous methods. Error analysis for the case of two dimension are considered. Finally, we also give some numerical examples to compared with existing methods.